Program Kesehatan Masyarakat Desa Dalam Meningkatkan Kualitas Kesehatan Masyarakat di Dusun Godean - Priasmoro, Dian Pitaloka; Asri, Yuni (Kolaborasi: Jurnal Pengabdian Masyarakat, 2024)
Introduction: Community health focuses not only on disease prevention and health promotion, which can significantly reduce the burden of disease and health care costs. The PKMD program is one of the appropriate approach methods used for the community based on the principles of mutual cooperation and self-help to help themselves solve problems in order to achieve a healthy and prosperous life. Objective: The PKMD program is also used by the D-III Nursing Study Program as an approach to improve the health status of the community in Godean Hamlet, Kucur Village, Dau District, Malang Regency. Method: PKMD activities are carried out for 3 weeks directly by students accompanied by lecturers. The activity began with socialization to local policy makers such as the Village, and Puskesmas, as well as village officials including RT, RW, and Hamlet. Result: Early detection of non-communicable diseases (NCDs) and community movement activities became the leading activities during the implementation of activities, which were enthusiastically followed by all residents. Conclusion: The program succeeded in increasing health awareness, promoting healthy lifestyles, and encouraging active participation of residents in maintaining environmental cleanliness. These activities demonstrate the importance of community cooperation in achieving shared health and wellness goals.